The effectiveness of using problem-based learning e-worksheet integrated with socio-scientific issues to improve critical thinking skills - Amalia, Ayu; Wiyatmo, Yusman (IAIN Palangka Raya, 2025)
This study aims to see the effectiveness of the PBL model student worksheets integrated with socio-scientific issues to improve critical thinking skills. The experimental design is using pre-experimental design with a one-group pretest-posttest type. The research subjects used were students in class X high school in Yogyakarta as many as 32 students. The results showed that. Data analysis to see the effectiveness is using normalized gain and paired sample t-test. The results of the study found that the use of problem-based learning-based student worksheets integrated with socio-scientific issues on global warming material can improve critical thinking skills seen from the N-gain value of 0.300 in the moderate category. In addition, the results of the statistical test showed that there was a significant difference in the pretest and posttest results. Therefore, it can be concluded that the problem-based learning student worksheet integrated with socio scientific issue is effective to improve critical thinking skills.